Mechanical characterization of masonry built with iCEBs of granite residual soils with cement-lime stabilization - Briga-Sá, Ana (2022)
The environmental impact due to the overexploitation of nonrenewable resources, the processing and transportation of materials, and waste production is a global concern that the construction industry must urgently address, since it is among the greatest contributors. Earth construction can be seen as an alternative building solution, enhancing sustainability, despite traditional techniques being nowadays in disuse in most developed countries. Construction with interlocking compressed earth blocks (iCEBs) is a recently developed technique, put in evidence in the last few decades, for overcoming many earth construction limitations. Here, this technique is studied as a sustainable building solution for Northern Portugal, where the typical soils are sandy, granitic residual soils with low clay content. These soils typically demand cement stabilization to produce earthen materials, which compromise the sustainability of the construction solution. In order to improve sustainability, stabilization with hydraulic lime is proposed as a partial replacement of cement. For this purpose, the properties of the selected soil were characterized through a set of geotechnical tests, with different percentages of cement and lime in the mixture composition tested, concerning the compressive strength of the specimens. A mixture composed of 87.5% of soil, 7.5% of cement, and 5% of lime was shown to be the most suitable for producing iCEBs with adequate mechanical performance. The compressive behavior of the iCEBs masonry was characterized by testing prisms and wallettes, considering both dry stack and mortar joints cases. The obtained results showed that using mortar in the bed joints allows for the improvement of the compressive strength (a 5%–18% increase) and Young’s modulus (a 65%–92% increase) of the masonry. Thus, it can be concluded that masonry built with locally produced iCEBs and stabilized with cement and lime is a feasible building solution, for a sustainable earth masonry built from sandy granitic residual soils, where the mechanical behavior is substantially enhanced by using bed-joint mortar.